Decoding Indigenous Justice Practices as a Pathway to Restorative Legal Reform in Southeast Asia - Pangeran Maulana Kamal (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
The legal system in Southeast Asia faces the challenge of balancing a retributive, punishment-oriented paradigm with the societal need for restorative justice. Amid modern legal reform efforts, customary justice practices offer a conceptual alternative rooted in the values of social harmony, deliberation, and moral balance. This research aims to interpret customary justice practices as a path to restorative legal reform in Southeast Asia, by examining the traditional legal system as a living source of legal values. This study uses a socio-legal approach with a qualitative method, through a case study on the Cirebon Customary Justice system regulated in the Cirebon Pepakem. Data was collected through field observations, interviews, and document studies, with interviews conducted with 10 informants consisting of indigenous leaders, legal academics, and judicial officials. Thematic analysis is used to identify principles of customary justice that are relevant to modern restorative law concepts. The results of the study show that the Cirebon Pepakem contains principles of social recovery, shared responsibility, and the idealism of fair judges, reflected through the symbols of Candra, Tirta, Cakra, and Sari. These values show that the traditional legal system of the archipelago has a restorative foundation that can potentially be integrated into contemporary legal reform. This study concludes that recognizing customary justice is a strategic step in building a contextual and sustainable restorative legal system in Southeast Asia.